The Socioeconomic Life of Coconut Farming Families (Cocos Nucifera L) in Improving the Standard of Living in Negeri Soahuku, Amahai District, Central Maluku Regency - Lumasiang, Yandro; Pinoa, Wiclif Sepnath; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2023)
Research has been conducted on the socio-economic condition of the coconut farming family (Cocos nucifera L) in improving the standard of living in Soahuku Country, Amahai District, Central Maluku Regency with the formulation of the problem of how coconut business (Cocos nucifera L) is used as a copra in improving the standard of living in Soahuku Country. This research aims to discover the role of coconut (Cocos nucifera L) in Soahuku Country. The variables researched are necessities of life, coconut production (Cocos nucifera L), copra marketing, income and sales results of copra, housing, education, and health. The type of research used by the survey method with the research location is the Soahuku Country. The time used in this study was one month with a population of 30 coconut farmers (Cocos nucifera L), and the sample used was random sampling with the number of samples taken by 15 farmers. The data collection techniques used are observations, questionnaires, and documentation. Based on the result of research conducted by the landing of coconut farmers (Cocos nucifera L), it is very dependent on the land area, and the selling price of copra is often erratic. The coconut business (Cocos nucifera L) can improve the standard of living.